1990
DOI: 10.1111/j.1476-5381.1990.tb14093.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between endothelin‐1 binding site densities and constrictor activities in human and animal airway smooth muscle

Abstract: 1Endothelin-1 (ET-1) binding site densities and constrictor activities were compared in airway smooth muscle preparations of human, guinea-pig, rat and mouse. 2 The mean contractile response to 0.3 pM ET-1 (measured as the % maximum response to 10puM carbachol, % C,.., + s.e.mean) and the mean concentration of ET-1 producing 30% C,.,. (95% confidence limits) were respectively; 85.9 + 5.4% and 3.4nM (2.4-5.0) for mouse trachea (n = 11), 88.8 + 4.7% and 18.2nM (11.2-25.2) for rat trachea (n = 6), 71.0 + 7.1% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
2
3

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 17 publications
7
73
2
3
Order By: Relevance
“…The reasons for this discrepancy are unclear at present, but it might be attributed to differences in tissue preparations (use of tracheal rings or segments in the previous studies versus zig-zag strips in the experiments of Maggi et al, 1989, and helical strips in the present study) and/or to differences in the experimental protocols (lower initial load, different incubation buffers and exposure of the tissues to high concentrations of KCI or carbachol before studying the effects of ET-1 in the previous experiments) in addition to the different strains of guinea-pig used. ET-1 appeared to be more potent in our tracheal preparations (estimated EC50 24.4nM) than was previously reported (estimated EC50 values of 50-60nM in the experiments of Hay, 1990 andHenry et al, 1990). Another possibility might be that inhibition of prostaglandin synthesis by indomethacin is heterogeneous in lung tissue as was previously reported for the kidney (Attallah & Stahl, 1980).…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…The reasons for this discrepancy are unclear at present, but it might be attributed to differences in tissue preparations (use of tracheal rings or segments in the previous studies versus zig-zag strips in the experiments of Maggi et al, 1989, and helical strips in the present study) and/or to differences in the experimental protocols (lower initial load, different incubation buffers and exposure of the tissues to high concentrations of KCI or carbachol before studying the effects of ET-1 in the previous experiments) in addition to the different strains of guinea-pig used. ET-1 appeared to be more potent in our tracheal preparations (estimated EC50 24.4nM) than was previously reported (estimated EC50 values of 50-60nM in the experiments of Hay, 1990 andHenry et al, 1990). Another possibility might be that inhibition of prostaglandin synthesis by indomethacin is heterogeneous in lung tissue as was previously reported for the kidney (Attallah & Stahl, 1980).…”
Section: Resultscontrasting
confidence: 53%
“…Analysis of the incubation medium showed that the basal release of TXA2 was in the 150-300pg range (Table 1) (0) (1-10nM), whereas no significant inhibition was seen at higher ET-1 concentrations (50-300nM) in the guinea-pig trachea in vitro (Maggi et al, 1989). Recently, indomethacin (5puM) has been reported to enhance the myotropic action of ET-1 in the guinea-pig trachea (Hay, 1990;Henry et al, 1990). The reasons for this discrepancy are unclear at present, but it might be attributed to differences in tissue preparations (use of tracheal rings or segments in the previous studies versus zig-zag strips in the experiments of Maggi et al, 1989, and helical strips in the present study) and/or to differences in the experimental protocols (lower initial load, different incubation buffers and exposure of the tissues to high concentrations of KCI or carbachol before studying the effects of ET-1 in the previous experiments) in addition to the different strains of guinea-pig used.…”
Section: Resultsmentioning
confidence: 99%
“…Selective inhibition of ET-J-induced contractions by NDGA As shown previously (Henry et al 1990b;1992 required to induce a contraction of 50% Cmax was 29 nM (95% confidence limits, 17-51 nM, n = 6). ET-1-induced contractions were concentration-dependently inhibited by NDGA ( Figure la).…”
Section: Functional Studiesmentioning
confidence: 99%
“…ET-1 initiates contraction by guinea-pig (Hay, 1992). In addition, recent autoradiographic, stimulating high affinity receptors located on the surface biochemical and functional studies indicate that ET-1-membrane of the airway smooth muscle cells (Turner et al, induced contractions in rat trachea appear to bc mediated by 1989; Henry et al, 1990b;Mattoli et al, 1991). At least two both ETA and ETB receptor-effector systems (Henry, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation